The relationship of gender with attitudes toward physical activity, level of physical activity, and aerobic capacity among medical students - Al-Rajaibi, Hajar; Al-Toubi, Khoula; Aljaadi, Said; Jaju, Sanjay; Jaju, Deepali (Frontiers in Psychology, 2026)
Introduction/ObjectiveCounseling about physical activity (PA) by doctors is influenced by their own attitudes towards physical activities and personal aerobic capacity levels. The study aims to explore ‘gender-specific relationship’ in Attitude Towards PA (ATPA), self-reported PA levels and Aerobic Capacity levels among senior medical students.MethodsIn this cross-sectional study (n=110; males 55; age 21.39 SD 0.939 years), ATPA was measured using a fifty-four-items Kenyon questionnaire; and self-reported PA level using International Physical Activity Questionnaire-Short Form (IPAQ-SF). The estimated aerobic capacity level was measured using Chester step test (CST).ResultsBoth genders showed a positive overall Kenyon score for ATPA (Females: Males 3.31:3.33). Females scored higher in the domains of health and fitness (4.15 vs 3.75, p<0.001); and reduction of tension (3.59 vs 3.32, p<0.012) whereas males scored higher in the domains of pursuit of vertigo (2.71 vs 3.06, p=0.001) and in tension and risk (2.7 vs 2.94, p=0.011). Estimated aerobic capacity using CST showed that males had (48.37 SD 10.11) higher score than females (40.35 SD 5.77; p<0.001; mean difference 8.02). IPAQ-SF analysis categorized 64% students having moderate level of PA but it did not correlate with estimated aerobic capacity measurement using CTS.ConclusionDespite both genders having an equally positive overall ATPA, females prioritized health and stress reduction, while males value thrill and risk. The gap between attitude and PA behavior needs tailored, gender-specific intervention strategies.